1288. Evaluation of Predictors for Clinical Success in Patients Treated with Eravacycline for Various Infections. (4th December 2021) - Alosaimy, Sara; Morrisette, Taylor; Lagnf, Abdalhamid M; Molina, Kyle; Bouchard, Jeannette; Gore, Tristan; Kang-Birken, Lena; Hobbs, Athena L; Perkins, Nicholson; Claeys, Kimberly C; King, Madeline; Pullinger, Benjamin; et al.
Abstract: Background: Eravacycline (ERV) is approved in the United States (US) for the treatment of complicated intra-abdominal infections in adults. We aimed to evaluate the independent predictors of clinical success in patients treated with ERV for various infections. Methods: Multicenter, retrospective, observational study conducted from September, 2018 to April, 2021. We included adults treated with ERV for ≥ 72hours. Clinical success was defined as 30-day survival, lack of 30-day infection-recurrence, and resolution of infection signs/symptoms. All outcomes were measured from ERV initiation. Multivariable logistic regression (MLR) was performed to identify independent predictors of clinical success. Clinically relevant variables were selected for model entry based on bivariate comparisons (P< 0.2) in a backward fashion. Results: We included 223 patients from 16 medical centers in 13 geographically unique states. The median (IQR) age was 61 (50-69) years, 57% were male and 62% were Caucasian. Median (IQR) APACHE II, and Charlson Comorbidity scores were 15 (10-21), and 3 (1-5), respectively. Sources of infection were primarily intra-abdominal (27%) and respiratory (27%). Common pathogens included Acinetobacter baumannii (21%) and those of the Enterobacterales order (36%). Infectious diseases consultation and surgical interventions were obtained in 93.7% and 52% respectively. Clinical success occurred in 64%, specifically 30-day survival in 78%, absence of 30-day infection-recurrence in 93%, and 74% experienced resolution of infection signs/symptoms. Since characteristics and outcomes were similar among various pathogens, MLR was conducted using the overall cohort. Skin as a source and combination therapy with ERV were independently associated with higher clinical success: odds ratio 3.3 [CI 1.1-10.2] and 2.9 [1.4-5.9], respectively. Whereas, ICU admission at culture time and undergoing surgery within 30 days of culture were independently associated with reduced odds of clinical success: 0.4 [0.17-0.80] and 0.3 [0.11-0.63] respectively. Conclusion: Although most ERV treated patients experienced clinical success, factors independently associated with higher clinical success are crucial to consider for optimum antibiotic selection. Disclosures: Kimberly C. Claeys, PharmD, GenMark (Speaker's Bureau) Madeline King, PharmD, tetraphase (Speaker's Bureau) Michael P. Veve, Pharm.D., Cumberland (Grant/Research Support)Paratek Pharmaceuticals (Research Grant or Support) Bruce M. Jones, PharmD, BCPS, Abbvie (Consultant, Advisor or Review Panel member, Speaker's Bureau)La Jolla (Speaker's Bureau)Melinta (Consultant)Merck (Consultant)Paratek (Consultant, Speaker's Bureau) Susan L. Davis, PharmD, Nothing to disclose Michael J. Rybak, PharmD, MPH, PhD, Paratek Pharmaceuticals (Research Grant or Support)